2016
DOI: 10.17795/ijpbs-1250
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive-Behavioral Group Therapy on Anger and General Health of Female Students in Iran: A Pilot Study

Abstract: Background: There is a growing body of literature in favor of cognitive therapy on anger in the world. Objectives: The aim of the present study was to evaluate the efficacy of cognitive-behavioral group therapy in the reduction of state-trait anger and increase of general health among female students of Khorasgan Azad University, Isfahan. Materials and Methods: This study was a quasi-experimental research. A number of 40 students from the humanity sciences faculty of Khorasgan Azad University, who accepted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This sensory system is composed of receptors and connecting neurons from the five senses (hear, see, smell, taste, and feel), and the area that processes visual information is the occipital lobe and is actively connected to the prefrontal cortex as the center of rational thinking. 11 The tool serves to facilitate the continuity of the learning process based on the principle that the knowledge possessed by every human being is received or captured through the senses, where someone can remember 50% of what was seen and heard. The result is consistent with Dale's learning experience, which stated that in learning, humans use 75% visual and 13% audio sensory, so the more senses are used to receive information, the more clear the knowledge obtained.…”
Section: Flashcardmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensory system is composed of receptors and connecting neurons from the five senses (hear, see, smell, taste, and feel), and the area that processes visual information is the occipital lobe and is actively connected to the prefrontal cortex as the center of rational thinking. 11 The tool serves to facilitate the continuity of the learning process based on the principle that the knowledge possessed by every human being is received or captured through the senses, where someone can remember 50% of what was seen and heard. The result is consistent with Dale's learning experience, which stated that in learning, humans use 75% visual and 13% audio sensory, so the more senses are used to receive information, the more clear the knowledge obtained.…”
Section: Flashcardmentioning
confidence: 99%
“…11 Another research was done by Sasmita showed that cognitive ability in low self-esteem schizophrenic patients has significantly increased after CBT by17,14 with …”
mentioning
confidence: 99%